2011
DOI: 10.1007/s11270-011-0902-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Green Waste Compost and Mycorrhizal Fungi on Calcium, Potassium, and Sodium Uptake of Woody Plants Grown Under Salt Stress

Abstract: Sodium chloride is the most often used chemical to malt ice and snow on the roads and has negative effects on the roadside environment. Searching for ways to improve the conditions for growth of trees and shrubs near the roads becomes an urgent matter. One such method of improving growth conditions for plants under salinity might be to use organic matter (green waste compost) and mycorrhizal fungi. This study studied the effect of application in soil different salts on several trees and shrubs growth in growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…However, compared with control, no significant difference of leaf K content was observed in 'Helmond Pillar','Mini',and 'Talago' in both EC 5 and EC 10,'Celeste' and 'Rose Glow' in EC 5,and 'Kasia' in EC 10. Similar results have been documented by Marosz (2012) showing that the leaf K content of B. thunbergii 'Atropurpurea' seedlings did not change when irrigated with tap water containing 3.3 g • L -1 (56.4 mM) NaCl or 6.0 g • L -1 CaCl 2 (54.1 mM). In addition, leaf K content of 'Maria' in both EC 5 and EC 10 and 'Celeste' and 'Rose Glow' in EC 10 increased with saline solution applied.…”
Section: Cultivarssupporting
confidence: 87%
See 2 more Smart Citations
“…However, compared with control, no significant difference of leaf K content was observed in 'Helmond Pillar','Mini',and 'Talago' in both EC 5 and EC 10,'Celeste' and 'Rose Glow' in EC 5,and 'Kasia' in EC 10. Similar results have been documented by Marosz (2012) showing that the leaf K content of B. thunbergii 'Atropurpurea' seedlings did not change when irrigated with tap water containing 3.3 g • L -1 (56.4 mM) NaCl or 6.0 g • L -1 CaCl 2 (54.1 mM). In addition, leaf K content of 'Maria' in both EC 5 and EC 10 and 'Celeste' and 'Rose Glow' in EC 10 increased with saline solution applied.…”
Section: Cultivarssupporting
confidence: 87%
“…The highest Cl concentration (68.1 mg • g -1 DW) was found in 'Maria' barberry in EC 10. Marosz (2012) reported that leaf Na content of B. thunbergii 'Atropurpurea' seedlings irrigated with tap water containing 3.3 g • L -1 (56.4 mM) NaCl for eight times at 7-day intervals increased 15 times compared with that containing 0 mM NaCl, but the leaf Ca concentration did not change; however, when the plants were irrigated with tap water containing 10.5 g • L -1 Na 2 CO 3 (100 mM), the leaf Na increased 17.5 times and Ca concentration decreased by 24%. Both studies consistently showed that barberry plants preferentially uptake Na instead of Ca when they were grown at elevated salinity conditions.…”
Section: Cultivarsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMF were widely found in the rhizosphere soil of Artemisia argyi [47,48], which is the main species of understory vegetation under gaps in Pinus tabulaeformis plantations. In addition, AMF colonization was found in Spiraea Linn [49] and Anemone L. [50]. In our study, the AMF PLFA 16:1w5c was higher in the medium gap compared to the forest canopy.…”
Section: Discussionsupporting
confidence: 53%
“…Values in a column with the same letter are not significantly different according to the LSD at P < 0.05 using Duncan's multiple-range test. (Marosz, 2012). Positive correlation between soil organic matter content and B adsorption has also been found (Hue et al, 1988).…”
Section: Resultsmentioning
confidence: 77%